Short report on a rescue excavation of a prehistoric and Árpádian Age site near Tura (Pest County, Hungary) - Simon, Bence; Joháczi, Szilvia; Kis, Zita (Dissertationes Archaeologicae, 2019)
The staff of the Institute of Archaeological Sciences of Eötvös Loránd University conducted a rescue excavation in the northern territory of Tura (Pest County, Hungary) in the spring and autumn of 2018. The works revealed settlement and burial features of the Late Bronze and Early Iron Age, settlement features of the Árpádian Age, one feature from the early modern period, and some traces of military activity in the Second World War. The unexpected scientific novelty of the excavation is the discovery of an extensive Árpádian Age settlement and a brick oven in one of the pit-houses.